2016
DOI: 10.1039/c5ra25954a
|View full text |Cite
|
Sign up to set email alerts
|

Production of phenolics via photocatalysis of ball milled lignin–TiO2 mixtures in aqueous suspension

Abstract: This work demonstrates the production of value added phenolics and aromatics via UV photocatalysis of lignin–TiO2 mixtures prepared by wet ball milling using different solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 43 publications
6
42
0
Order By: Relevance
“…The main drawback of these processes has been lower conversion into valueadded chemical-richl iquid products along with al arger fraction of solid byproducts. [102,103] The reactions resulted in selectiveg eneration of industrially valuable phenolics, such as guaiacol, vanillin, and isoeuginol. [100] Initial photocatalytic studies of lignin primarily dealt with demineralization reactions, but have now shifted towards selective conversion into aromatic compounds.…”
Section: Chemicals From Biomassmentioning
confidence: 99%
See 3 more Smart Citations
“…The main drawback of these processes has been lower conversion into valueadded chemical-richl iquid products along with al arger fraction of solid byproducts. [102,103] The reactions resulted in selectiveg eneration of industrially valuable phenolics, such as guaiacol, vanillin, and isoeuginol. [100] Initial photocatalytic studies of lignin primarily dealt with demineralization reactions, but have now shifted towards selective conversion into aromatic compounds.…”
Section: Chemicals From Biomassmentioning
confidence: 99%
“…[99][100][101] Biomass chemical composition is highly complex and non-uniform,w hich also creates ab ig problem in establishing areliable consistent techniquefor generation of highly valuable chemical compounds.L ignin is considered am ajor byproduct of biorefineries and the paper-pulp industry and is ar ich source of aromatic compounds. [102,103] Electron and hole formation was found to be key for both the catalytic reactions to proceed, althought he photocatalytic reaction was based on surfacee xcitation,w hereas bulk excitation was observed in the thermocatalytic reaction. Similarly,t hermocatalytic conversion of lignin has been primarily carriedo ut by using zeolitesr ich in acidic sites, which resulted in higher selectivity to and generation of aromatics.…”
Section: Chemicals From Biomassmentioning
confidence: 99%
See 2 more Smart Citations
“…The degradation stage refers to the results of a study reported by 27 . A total of 20 mL lignin solution of OPEFB with a concentration of 4 ppm was put into 5 vials and each added 0.5 g of TiO 2 .…”
Section: Lignin Degradation Of Opefbmentioning
confidence: 99%